Phobos and Deimos surface composition: search for spectroscopic analogues. Issue 1 (10th August 2022) - Poggiali, Giovanni; Matsuoka, M; Barucci, M A; Brucato, J R; Beck, P; Fornasier, S; Doressoundiram, A; Merlin, F; Alberini, A
ABSTRACT: Phobos and Deimos, the two satellites of Mars, were largely studied in the past using ground-based telescope and spacecraft data, although most of the data were obtained by opportunity observations performed by Mars dedicated orbiters. Despite the data available so far, the main composition of the two moons is not yet fully understood. The possible presence of hydrated minerals along with mafic minerals olivine and pyroxene seems to be the most plausible interpretation, but more investigations are needed. MIRS spectrometer on-board the future JAXA MMX sample return mission will help to unveil the open question on the composition of Phobos and Deimos. In this work, we review past spectroscopic observations of the Martian moons, both from ground observatories and spacecraft data set, aiming at better understanding the constraints in interpreting the Mars satellites composition and at identifying the best spectroscopic analogues. We also present new laboratory measurements on mineral mixing and meteorites to match the satellites spectral behaviour. New measurements were acquired at INAF-Astrophysical Observatory of Arcetri and IPAG laboratories at room conditions exploring different geometries and the results obtained set new constraints for future laboratory measurements. Our preliminary results confirm that the surface of Phobos and Deimos can be associated with samples characterized by a higher presence of dark components (e.g. amorphous carbon) or minerals produced by space weathering (e.g. Fe0 and FeS-bearing materials). Presence of dark component could also be totally responsible for the reduced hydrated band observed on the moons without invoking dehydration or OH-implantation on anhydrous surface.